Pregnancy Among Women with Kidney Transplantation: A 20-Years Single-Center Registry - Stephanye Mariano; Jose Paulo de Siqueira Guida; Marcos Vinicius de Sousa; Mary Angela Parpinelli; Fernanda Garanhani Surita; Marilda Mazzali; Maria Laura Costa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To assess maternal and perinatal outcomes in pregnancies after kidney transplantation in a tertiary center in Brazil. Methods Retrospective cohort of pregnancies in women with kidney transplantation at the Universidade Estadual de Campinas, from January 1995 until December 2017. Medical charts were reviewed, andmaternal and perinatal outcomes were described as means and frequencies. Renal function and blood pressure were evaluated during pregnancy and postpartum. Results A total of 22 women had at least 1 pregnancy during the considered timeinterval, and 3 of them had > 1 pregnancy, totalizing 25 pregnancies. The mean age at transplantation was of 24.6 ± 4.2 years old, and the mean time interval until pregnancy was of 67.8 ± 46.3months. Themost frequent complication during pregnancywas hypertension, which affected 11 (64.7%)women. The gestational age at delivery was 34.7 ± 4weeks, and 47% of these pregnancies were preterm (< 37 weeks). A total of 88.2% of the women delivered by cesarean section. Renal function, measured by serum creatinine, remained stable during pregnancy, and the systolic blood pressure increased significantly, while the diastolic blood pressure did not differ during pregnancy. Conclusion Pregnancy after kidney transplantation is a rare event. Pre-eclampsia and prematurity were frequent complications, and cesarean section rates were very high. A specialized antenatal and postpartum care with a multiprofessional approach and continuous monitoring of graft function are essential for the early diagnosis of complications and improved outcomes.